Consistent individual differences in the social phenotypes of wild great tits, Parus major. (October 2015) - Aplin, L.M.; Firth, J.A.; Farine, D.R.; Voelkl, B.; Crates, R.A.; Culina, A.; Garroway, C.J.; Hinde, C.A.; Kidd, L.R.; Psorakis, I.; Milligan, N.D.; Radersma, R.; et al.
Abstract : Despite growing interest in animal social networks, surprisingly little is known about whether individuals are consistent in their social network characteristics. Networks are rarely repeatedly sampled; yet an assumption of individual consistency in social behaviour is often made when drawing conclusions about the consequences of social processes and structure. A characterization of such social phenotypes is therefore vital to understanding the significance of social network structure for individual fitness outcomes, and for understanding the evolution and ecology of individual variation in social behaviour more broadly. Here, we measured foraging associations over three winters in a large PIT-tagged population of great tits, and used a range of social network metrics to quantify individual variation in social behaviour. We then examined repeatability in social behaviour over both short (week to week) and long (year to year) timescales, and investigated variation in repeatability across age and sex classes. Social behaviours were significantly repeatable across all timescales, with the highest repeatability observed in group size choice and unweighted degree, a measure of gregariousness. By conducting randomizations to control for the spatial and temporal distribution of individuals, we further show that differences in social phenotypes were not solely explained by within-population variation in local densities, but also reflected fine-scale variation in social decision making. Our results provide rare evidence of stable social phenotypes in a wild population of animals. Such stable social phenotypes can be targets of selection and may have important fitness consequences, both for individuals and for their social-foraging associates. Highlights: Social networks may be useful to quantify individual differences in sociality. We test this by measuring individual consistency in replicated social networks. A population of 729–1053 great tits was sampled a total of 41 times over 3 years. Individuals showed relatively high consistency in social network position. Controlling for space use found individual variation in fine-scale social behaviour.